Experimental Investigations on Magnetic Abrasive Finishing of SS 304L - Kanish, T.C.; Kuppan, P.; Narayanan, S. (Applied Science and Engineering Progress, 2013)
Magnetic Abrasive Finishing (MAF) is a super finishing technique, employs the magnetic force and magnetic abrasive for finishing variety of engineering materials. This paper presents the development of experimental setup to carryout MAF operations in a flat Stainless Steel grade 304L material. Experimentation was planned according to Taguchi’s L16 (42) design of experimentation technique. The different cutting conditions selected for the investigations are: voltage applied to electromagnet, machining gap, rotational speed of electromagnet and mixing ratio (Fe+; Al2O3). Surface finish and percentage improvement in surface finish (%Δ Ra) were estimated after each experiment. From the experimental results it was found that the average surface finish value has been achieved as low as 0.09 μm.